Komodifikasi Novel pada Platform Sastra Siber: Studi Pragmatisme Penulis Novel di Aplikasi Fizzo - Fahmy, Zulfa; Rohman, Fathur; Pristiwati, Rahayu (GERAM: Gerakan Aktif Menulis, 2023)
This research aims to explain and analyze the commodification of novels on the Fizzo cyber literary platform, understand the role of pragmatism in the commodification process, and provide insight into the impact of commodification on cyber literary novels. Novels have become commodities through commodification on the Fizzo cyber-literary platform. Cyberliterary platforms offer economic benefits to novel writers. Novel writers who do not have good marketing skills think pragmatically about publishing novels on cyber-literary platforms. Therefore, it is necessary to research pragmatism in the commodification of novels on the Sibe Fizzo literary platform. The formulation of this research problem is: how are novels commodified on the Fizzo cyber literary platform? How does the author's pragmatism play a role in the commodification of the novel on cyber-literary platforms? This research uses a qualitative descriptive design with observations and interviews as the main data. The data were analyzed using hermeneutic analysis. The results of this research show that commodification on the Fizzo cyber literary platform includes offering economic benefits, characteristics of popular literary novels, genre division, and intensive promotion on the internet. Novel writers on the Fizzo cyber literary platform are oriented towards readers' tastes. This can be seen from the characteristics of novels, which have simple plots, tend to be clichés, use controversial issues, have regular publication schedules, and use language trends. This situation has implications for the quality of novels on cyber-literary platforms that are uncontrolled and subordinate to the market. However, the openness of interaction between readers and writers is a discourse that continues to develop, which is the basis for the creative process of novel writers to innovate on the Fizzo cyber literary platform.